The Influence of Content Marketing, Message Framing, and Brand Image on Student Interest in Using Bank Syariah Indonesia Services in Solo Raya - Anggraheni, Inawati Nur Erlita (Presscience, 2024)
The objective of this study is to examine whether content marketing, message framing, and brand image influence the interest of students in Solo Raya in utilizing the products and services of Bank Syariah Indonesia. This research employs a quantitative methodology, with the sample selected through non-probability sampling, focusing on students from five universities in Solo Raya. Data collection was conducted using a questionnaire with a Likert scale measurement, resulting in 1200 valid responses. The data analysis method utilized is Structural Equation Modeling (SEM) with the assistance of SPSS software. The findings reveal that content marketing and brand image have a positive impact on students' interest in using BSI's products and services, while message framing does not significantly influence their interest.